2022
DOI: 10.1002/ldr.4429
|View full text |Cite
|
Sign up to set email alerts
|

The effect of tree species on soil organic carbon recovery in a restoration project is associated with vegetation biomass: Evidence from the Pingshuo Mine reclaimed ecosystem, North China

Abstract: Vegetation and soil surveys were made within three mixed forests and four monoculture forests on opencast coal mine spoils in the Loess Plateau (China) to reveal the tree species effect on reclaimed mine soil (RMS) and carbon (C) sequestration.Results showed that tree biomass, annual litter biomass, and reserved litter biomass varied among forests, with Robinia pseudoacacia L.-Pinus tabuliformis Carr. recording the highest tree biomass, leaf C, and leaf nitrogen (N) values. The greatest C and N contents in RMS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 64 publications
0
4
0
Order By: Relevance
“…The results of SSI also indicated that the implementation of phytomanagement near tailings with severe soil erosion can stop soil degradation and improve soil structural stability. Revegetation as an effective phytomanagement measure has been shown to improve soil physical properties and anti-erodibility in vulnerable ecological mining regions (Alvarez-Rogel et al 2021; Yuan et al 2022;Zhang et al 2015). We also found that forests were more effective than natural grasslands in improving the water stability of soil aggregates, possibly due to the fact that tree plantings produce more WSA than herbs and shrubs.…”
Section: Effects Of Phytomanagement On Soil Aggregationmentioning
confidence: 53%
“…The results of SSI also indicated that the implementation of phytomanagement near tailings with severe soil erosion can stop soil degradation and improve soil structural stability. Revegetation as an effective phytomanagement measure has been shown to improve soil physical properties and anti-erodibility in vulnerable ecological mining regions (Alvarez-Rogel et al 2021; Yuan et al 2022;Zhang et al 2015). We also found that forests were more effective than natural grasslands in improving the water stability of soil aggregates, possibly due to the fact that tree plantings produce more WSA than herbs and shrubs.…”
Section: Effects Of Phytomanagement On Soil Aggregationmentioning
confidence: 53%
“…Carbon sequestration in a soil is strictly and positively related to vegetation biomass (Yuan et al 2022 ). The found in our study increase in stocks of SOM and of particular elements is typical for the development of young forest stands, and is caused mainly by the increasing with stand age alimentation of tree litterfall to a topsoil (Grüneberg et al 2014 ; Jasińska et al 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…A set of restoration actions, such as revegetation, provides positive feedback on soil organic carbon accumulation and soil aggregation (Han et al, 2023; Tang et al, 2010); soil nutrients including carbon, nitrogen, and phosphorus (Bai et al, 2014; Hu et al, 2021; Song et al, 2022; Yuan et al, 2019); soil hydraulic conductivity (Ren et al, 2016); and soil moisture (Li et al, 2018). Different vegetation types used in rehabilitation influence the soil moisture and organic carbon (Gao et al, 2018; Mei et al, 2018; Yuan et al, 2022), saturated hydraulic conductivity, and soil water retention curves (Wu et al, 2023). The diversity of the aboveground communities was strongly and positively correlated with the variety of soil bacteria and eukaryotes (Delgado‐Baquerizo et al, 2018).…”
Section: Introductionmentioning
confidence: 99%